2019
DOI: 10.1038/s41598-019-51224-7
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a receptor guanylate cyclase expressed in the sperm flagella of stony corals

Abstract: The receptor guanylate cyclases (rGCs) in animals serve as sensitive chemoreceptors to detect both chemical and environmental cues. In reproduction, rGCs were shown to be expressed on sperm and serve as receptors for egg-derived sperm-activating and sperm-attracting factors in some echinoderms and mammals. However, sperm-associated rGCs have only been identified in some deuterostomes thus far, and it remains unclear how widely rGCs are utilized in metazoan reproduction. To address this issue, this study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Spermiogenesis is a process by which haploid spermatids undergo a complex series of morphological changes, and eventually become elongated functional sperm. The Testis-specific serine/threonine-protein kinase 1 CL2440.Contig1_All [78,79] Testis-specific serine/threonine-protein kinase 2 Unigene8363_All [78,79] Outer dense fiber protein 2 CL11766.Contig4_All [80] Alstrom syndrome protein 1 CL2440.Contig1_All [81] Radial spoke head 1 homolog CL2440.Contig1_All [82] Dynein regulatory complex protein 9 CL4871.Contig6_All [83] Sperm motility/capacitation Dynein regulatory complex subunit 7 CL8060.Contig33_All [86] Sodium/hydrogen exchanger 10 CL11505.Contig1_All [87] Creatine kinase, flagellar CL12240.Contig1_All [88] Adenylate cyclase type 10 CL1089.Contig3_All [87] Cation channel sperm-associated protein 3 Unigene27629_All [87] Cyclin-F Unigene55093_All [89] Dynein regulatory complex subunit 4 Unigene7541_All [90] Chromosome structure Histone H2A CL4659.Contig4_All [120] Fertilization process Hapless 2 CL1879.Contig3_All [109,110] Receptor guanylate cyclases CL4659.Contig4_All [22] Cyclic nucleotide-gated channel cone photoreceptor subunit alpha CL3457.Contig2_All [153] Steroidogenesis Steroid 17-alpha-hydroxylase/17,20 lyase Unigene38823_All [104] presence of spermaries having both round spermatids and mature sperm in testes collected in June 2017 suggested that spermiogenesis was occurring in the testes at the time of collection, and that genes involved in regulation of spermiogenesis were being expressed in testes.…”
Section: Characteristics Of Mature Testes As Assessed By Histologicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Spermiogenesis is a process by which haploid spermatids undergo a complex series of morphological changes, and eventually become elongated functional sperm. The Testis-specific serine/threonine-protein kinase 1 CL2440.Contig1_All [78,79] Testis-specific serine/threonine-protein kinase 2 Unigene8363_All [78,79] Outer dense fiber protein 2 CL11766.Contig4_All [80] Alstrom syndrome protein 1 CL2440.Contig1_All [81] Radial spoke head 1 homolog CL2440.Contig1_All [82] Dynein regulatory complex protein 9 CL4871.Contig6_All [83] Sperm motility/capacitation Dynein regulatory complex subunit 7 CL8060.Contig33_All [86] Sodium/hydrogen exchanger 10 CL11505.Contig1_All [87] Creatine kinase, flagellar CL12240.Contig1_All [88] Adenylate cyclase type 10 CL1089.Contig3_All [87] Cation channel sperm-associated protein 3 Unigene27629_All [87] Cyclin-F Unigene55093_All [89] Dynein regulatory complex subunit 4 Unigene7541_All [90] Chromosome structure Histone H2A CL4659.Contig4_All [120] Fertilization process Hapless 2 CL1879.Contig3_All [109,110] Receptor guanylate cyclases CL4659.Contig4_All [22] Cyclic nucleotide-gated channel cone photoreceptor subunit alpha CL3457.Contig2_All [153] Steroidogenesis Steroid 17-alpha-hydroxylase/17,20 lyase Unigene38823_All [104] presence of spermaries having both round spermatids and mature sperm in testes collected in June 2017 suggested that spermiogenesis was occurring in the testes at the time of collection, and that genes involved in regulation of spermiogenesis were being expressed in testes.…”
Section: Characteristics Of Mature Testes As Assessed By Histologicalmentioning
confidence: 99%
“…Upregulation of Hap2/ Gcs1 in E. ancora mature testes suggests that Hap2/ Gcs1 participates in scleractinian sperm-egg fusion. Most recently, we reported that receptor guanylate cyclase A (rGC-a) (also known as atrial natriuretic peptide receptor 1 in mammals) is expressed in E. ancora sperm flagella [22] (Fig. 5, Table 5).…”
Section: Upregulated Genes In Mature Testesmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of Hap2/Gcs1 in E. ancora mature testes suggests that Hap2/Gcs1 participates in scleractinian sperm-egg fusion. Most recently, we reported that receptor guanylate cyclase A (rGC-a) (also known as atrial natriuretic peptide receptor 1 in mammals) is expressed in E. ancora sperm agella [22] (Fig. 5, Table 5).…”
Section: Upregulated Genes In Mature Testesmentioning
confidence: 99%
“…Studies on molecular and cellular aspects of scleractinian gametogenesis have just recently begun. Only several reports are available describing genes related to oogenesis including vitellogenesis [12][13][14][15][16][17][18][19][20] and to spermatogenesis [21,22]. Currently, in order to cope with recent declines of coral reefs, reef restoration efforts via aquaculture are being initiated worldwide [23][24][25].…”
Section: Introductionmentioning
confidence: 99%